2021
DOI: 10.11621/pir.2021.0205
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Spatial Ability for Talent Identification, Educational Assessment, and Support: Evidence from Adolescents with High Achievement in Science, Arts, and Sports

Abstract: Background. Spatial ability (SA) is a robust predictor of academic and occupational achievement. The present study investigated the psychometric properties of 10 tests for measuring of SA in a sample of talented schoolchildren. Objective. Our purpose was to identify the most suitable measurements for SA for the purpose of talent identification, educational assessment, and support. Design. Our sample consisted of 1479 schoolchildren who had demonstrated high achievement in Science, Arts, or Sports. Several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 23 publications
(38 reference statements)
4
21
0
Order By: Relevance
“…Our results on differences between language group in intelligence are consistent with differences in achievement, intelligence and other psychological characteristic found between selected and unselected for prior achievement groups 40 , 61 , 53 . For example, one study 52 showed that STEM-selected adolescents demonstrated higher year grades and state exams results ( η p 2 = 0.05 and 0.23, respectively), compared with their unselected peers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results on differences between language group in intelligence are consistent with differences in achievement, intelligence and other psychological characteristic found between selected and unselected for prior achievement groups 40 , 61 , 53 . For example, one study 52 showed that STEM-selected adolescents demonstrated higher year grades and state exams results ( η p 2 = 0.05 and 0.23, respectively), compared with their unselected peers.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, several recent studies have pointed out that Year grade has a number of limitations, e.g. teacher bias towards students’ personality; and inability to distinguish between populations selected for high-achievement in Science and their peers (see Likhanov et al 54 , Papageorgiou et al 55 and Budakova et al 40 , for a discussion of the limitations of this grading system). See Appendix for descriptive statistics and correlations for these Year grades.…”
Section: Methodsmentioning
confidence: 99%
“…In other words, members of this culture feel threatened by ambiguous or unknown situations. This feature can significantly shape children's imagination development and the educational practices supporting it [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…specific patterns of the links between SA facets or centrality indices distributions within networks) are linked to success in STEM beyond links with individual differences in level of SA (e.g. Budakova et al, 2021; Wai et al, 2009). Furthermore, there might be sex differences in SA networks that exist above and beyond reported average sex differences in SA (Tosto et al, 2014), (Toivainen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%